GEOGRAFIA DELLA MEMORIA ODONOMASTICA DELLA GRANDE GUERRA - Arturo Gallia; Michele Castelnovi (Bollettino della Società Geografica Italiana, 2019)
At present there is no census of the geographic distribution of the entitling of streets in the Italian municipalities, with reference to the names that recall the places, events, dates or the people of the Great War. The authors propose a first attempt to examine the spatial distribution of this particular form of collective memory, doubly geographical because it refers to place names or toponyms (some river, some mountain) through street names or odonyms, setting the basis for the realization of a Great War odonyms geodatabase.